Optical and Structural Properties of Er/Sr Co-Doped αMnS Films Prepared by Chemical Spray Pyrolysis - Onyeka E. NNANYELUGO; Peter O. OFFOR; Cyril OCHERI; Camillus S. OBAYI (FUDMA Journal of Engineering and Technology, 2025)
Erbium/Srontium (Er/Sr) co-doped manganese sulphide (MnS) thin films were synthesized via chemical spray pyrolysis and characterized using UV-Vis, SEM/EDS, FTIR, and XRD. Optimal optical properties were observed at 10ml Er/Sr doping, with a reduced bandgap of 2.33 eV and improved absorbance. SEM revealed enhanced grain connectivity, while XRD confirmed the retention of cubic structure. These results suggest potential applications in optoelectronics. These films were made from a precursor solution containing 0.8451M manganese (II) sulphate (MnSO4.H2O), 0.1M thioacetamide (CH3CSNH2), 0.85M strontium hydroxide (Sr (OH)2), and 0.95M Erbium (III) chloride hexahydrate (ErCl3.6H2O), which were spray-coated on a glass substrate at constant temperature of 300°C. The samples were characterized using different techniques such as scanning electron microscope (SEM)/EDS, UV-Visible spectroscopy, Fourier transform infrared (FTIR), and X-ray diffraction (XRD) analysis. The SEM and EDS analysis revealed that moderate doping (≤10%) enhances grain connectivity and crystal growth in the sample, resulting in a more compact structure with improved crystallinity. The EDS indicate the elements in wt.% (%), the elemental composition such as Mn, S, Er, and Sr. The UV-Visible spectroscopy study revealed an improved optical property for all the samples, but it’s more prominent in the sample synthesized with 10ml Er/Sr. The FTIR result showed that some functional groups like C=O, C–H, N–H, S-O, Mn-S, and O-H were present. As revealed by XRD analysis revealed the physical interpretation of the crystal planes (111), (220), (200), (311), and (222), respectively.